The role of albumin-to-globulin ratio in undifferentiated arthritis: Rheumatoid arthritis versus primary Sjögren syndrome - Reyhan Köse Çobanoglu; Taşkın Şentürk (Archives of Rheumatology, 2022)
Objectives: This study aims to compare initial albumin-to-globulin ratio (AGR) in patients with rheumatoid arthritis (RA) and primary Sjögren syndrome (pSS) presenting with undifferentiated arthritis (UA) and to investigate whether there was a difference in terms of AGR between the two patient groups and healthy controls. Patients and methods: Between January 2019 and December 2019, a total of 177 patients including 96 RA (10 males, 86 females; mean age: 53.6±10.8 years; range, 21 to 74 years) and 81 pSS (5 males, 76 females; mean age: 53.2±14.1 years; range, 23 to 79 years) and 82 healthy controls (20 males, 62 females; mean age: 50.5±13.6 years; range, 20 to 79 years) were included in this case-control study. Demographic characteristics, albumin, and globulin levels of all participants were recorded. The AGR, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), anti-nuclear antibody (ANA), and anti-citrullinated protein antibodies (ACPA) were assessed. Results: The mean AGR was 1.50±0.16 in the control group, 1.48±0.24 in the RA group, and 1.30±0.23 in the pSS group, indicating a significant difference between the pSS and the other two groups (p<0.001). The receiver operating characteristic analysis revealed that the cut-off value for AGR was 1.39 (area under the curve=0.736) with a sensitivity of 0.642 and a specificity of 0.646 (p<0.001). The ESR and CRP values were higher (p<0.001), and ANA (p<0.001) and RF (p=0.003) positivity were lower in the RA group, compared to the pSS group. Conclusion: This study findings indicate that AGR is a helpful tool in the differential diagnosis of RA and pSS presenting with UA at the time of admission, and Sjögren syndrome should be considered in case of AGR ≤1.39.